The Returns to Computer Use Revisited: Have Pencils Changed the Wage Structure Too? - DiNardo, J. E.; Pischke, J.-S. (Quarterly Journal of Economics, 1997)
Are the large measured wage differentials for on-the-job computer use a true return to computer skills, or do they just reflect that higher wage workers use computers on their jobs? We examine this issue with three large cross-sectional surveys from Germany. First, we confirm that the estimated wage differential associated with computer use in Germany is very similar to the U. S. differential. Second, we also measure large differentials for on-the-job use of calculators, telephones, pens or pencils, or for those who work while sitting down. We argue that these findings cast some doubt on the literal interpretation of the computer use wage differential as reflecting true returns to computer use or skill.